Sosialisasi Strategi Peningkatan Kepatuhan Pembayaran Pajak dan Retribusi Daerah pada Badan Pendapatan Daerah Provinsi Sulawesi Tenggara - Nasrullah Dali; Emilia Nurdin; Tuti Dharmawati; Sulvariany Tamburaka; Hasnidar Hasnidar; Andi Muhammad Fuad Ramadhan; Si Made Ngurah Purnaman; Taufan Sufatriansa Awal; La Ode Muhammad Arfan Samrin; Dzulfikri Azis Muthalib (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Compliance with local tax and retribution payments plays a crucial role in increasing Regional Own-Source Revenue (PAD). However, low fiscal literacy and limited effectiveness of existing socialization programs remain major obstacles to achieving optimal revenue targets. This community service program aims to enhance the knowledge and capacity of officers at the Regional Revenue Agency (Bapenda) of Southeast Sulawesi Province in implementing more effective, persuasive, and adaptive socialization strategies. The methods used include direct observation, interviews, document analysis, material presentation, and interactive discussions. The results indicate that the socialization activities improved officers' understanding of tax literacy concepts, fiscal communication, and technology-based educational strategies. Additionally, the findings reveal that low public literacy, limited use of digital media, and varying public perceptions of fiscal transparency significantly influence taxpayer compliance. This program produced practical educational materials and strategic recommendations that can be sustainably implemented by Bapenda. Overall, the activity contributes positively to strengthening the agency’s internal capacity and refining socialization strategies to enhance taxpayer compliance and support optimal local revenue collection.